Tripled coincidence points for weakly compatible and its variants in fuzzy metric spaces - kaushik, preeti (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper, we will introduce the concept of weakly commuting and variants of weakly commuting mappings (R-weakly commuting, R-weakly commuting of type (Af), type (Ag), type (P) mappings) for triplet in fuzzy metric spaces. Secondly, we introduce the notion of weakly compatibility and its variants weakly f-compatible maps and weakly g-compatible maps. At the end, we prove common ï¬xed point theorems for a pair of weakly compatible map and their variants, which generalize the results of various authors present in ï¬xed point theory literature. Our result is validated with a suitable example.